2009
DOI: 10.1080/01426390903019841
|View full text |Cite
|
Sign up to set email alerts
|

City as Wilderness: The Wilderness Metaphor from Wilhelm Heinrich Riehl to Contemporary Urban Designers

Abstract: In this text we take a closer look at the development of the wilderness metaphor of the Zwischenstadt, that is, fragmented urban landscapes in Germany. We trace the metaphor's meanings back to its origins in the conservative cultural criticism of Wilhelm Heinrich Riehl of the mid-nineteenth century and analyse the different meanings of 'wilderness' in today's urban and landscape planners' positions. Our aim is to demonstrate that the meanings of the concept of wilderness, as well as those of city and cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 4 publications
2
10
0
1
Order By: Relevance
“…One such management goal is the creation of new parks using IGS where size and characteristics are suitable. These results are in line with earlier research that found Japanese respondents are overall hesitant to embrace the concept of urban wilderness, a concept that has figured prominently in work on IGS from Europe, North America and Australia [27,28,[39][40][41][42][43][44][45][46][47][48][49][50]. Yet this does not imply that residents do not perceive the value of IGS as a different kind of urban green space.…”
Section: Preferred Management Goalssupporting
confidence: 81%
“…One such management goal is the creation of new parks using IGS where size and characteristics are suitable. These results are in line with earlier research that found Japanese respondents are overall hesitant to embrace the concept of urban wilderness, a concept that has figured prominently in work on IGS from Europe, North America and Australia [27,28,[39][40][41][42][43][44][45][46][47][48][49][50]. Yet this does not imply that residents do not perceive the value of IGS as a different kind of urban green space.…”
Section: Preferred Management Goalssupporting
confidence: 81%
“…It can be shown that there are strong ethical and religious, educational and cultural motifs in the demand for wilderness. The ultimate conclusion of the thesis that wilderness is a "state of mind" (Nash, 2001) or a "mental construct" (Vincenzotti and Trepl, 2009) could be that even vegetation in a crack in the pavement or a bird singing in the city might be "wilderness" from a human perspective (Brouns, 2004). Hoheisel et al (2010) claim that "wilderness" is not a feature that can be described in natural scientific terms, and demand a cultural scientific approach.…”
Section: Wilderness: a New World Concept Meets Old Europementioning
confidence: 99%
“…They explain different angles that overwhelm the visitors to the site with their magnitude, be it the persistence of the place that has postponed the regeneration, the reminders of its past heritage or the powerful element of nature that opposes our supremacy over the urban environment. Vicenzotti and Trepl (2009) remind us that wilderness is a product of civilisation-a contrast between natural and man-made elements is needed in order to tell nature apart from culture. When man-made elements represent human supremacy over nature, then ''the category of the sublime makes it permissible to take pleasure in wild, sublime sceneries'' (Vicenzotti & Trepl, 2009, p. 382).…”
Section: The Sublimity Of Derelictionmentioning
confidence: 96%
“…The wilderness metaphor in the field of urban (landscape) design has recently been discussed by Vicenzotti and Trepl (2009). Although seemingly a set of powerful contrasts, the notions of city and wilderness in fact intertwine.…”
Section: The Wilderness Of Derelict Placesmentioning
confidence: 99%